High-Fidelity Perforator Visualization for Cadaver Dissection in Surgical Training - Wong, Allen Wei Jiat; Kok, Yee Onn; Chew, Khong Yik; Tan, Bien Keem (Archives of Plastic Surgery, 2023)
In the first half of the third century B.C., Herophilus and Erasistratus performed the first systematic dissection of the human body. For subsequent centuries, these cadaveric dissections were key to the advancement of anatomical knowledge and surgical techniques. To this day, despite various instructional methods, cadaver dissection remained the best way for surgical training. To improve the quality of education and research through cadaveric dissection, our institution has developed a unique method of perforator-preserving cadaver injection, allowing us to achieve high-fidelity perforator visualization for dissection studies, at low cost and high efficacy. Ten full body cadavers were sectioned through the base of neck, bilateral shoulder, and hip joints. The key was to dissect multiple perfusing arteries and draining veins for each section, to increase “capture” of vascular territories. The vessels were carefully flushed, insufflated, and then filled with latex dye. Our injection dye comprised of liquid latex, formalin, and acrylic paint in the ratio of 1:2:1. Different endpoints were used to assess adequacy of injection, such as reconstitution of eyeball volume, skin turgor, visible dye in subcutaneous veins, and seepage of dye through stab incisions in digital pulps. Dissections demonstrated the effectiveness of the dye, outlining even the small osseous perforators of the medial femoral condyle flap and subconjunctival plexuses. Our technique emphasized atraumatic preparation, recreation of luminal space through insufflation, and finally careful injection of latex dye with adequate curing. This has allowed high-fidelity perforator visualization for dissection studies.
Keywords: cadaver; high fidelity; dissection; perforator